Perkembangan Bahasa Anak: Analisis Komunikasi Siswa - Rohaina Rohaina (Cahaya Ilmu Cendekia Publisher, 2020)
Language is essentially speech of human thoughts and feelings on a regular basis, which uses sound as an intermediary in delivering messages. Language skills are human feelings through appropriate sounds, which are used together, interact, and identify in good conversations. In the process of language development, prior language skills have always been the basis for the development of the next language about such language development, discussion of language development in elementary school children becomes interesting to explore, especially how the language concept is. This article will discuss the analysis of children's language development in communication at school. The purpose in writing this article is to improve children's ability in language. In this data collection using the method of obsevation